Investigation into the Role of Forkhead Box A1 (FOXA1) in Late-Onset Preeclampsia of a Prospective Cohort Study and Its Actions on Trophoblast Invasion and Migration - Juan Zhu; Yunjian Wei; Zhen Wang; Qiuling Jie; Ping Long; Huamei Yang; Hui Ke; Zaijia Yang; Yanlin Ma (Clinical and Experimental Obstetrics & Gynecology)
Background: The primary objective was to investigate how Forkhead Box A1 (FOXA1) contributes to late-onset preeclampsia (LOPE) and its impact on trophoblast invasion and migration. Methods: The prospective cohort study included 15 pregnant women with LOPE (gestational age of ≥34+0 weeks), and 18 normal pregnant women. FOXA1 expression in placental tissues was determined by immunofluorescent and immunohistochemical (IHC) staining. FOXA1 mRNA and protein expression in HTR-8/SVneo was determined by real-time quantitative polymerase chain reaction (qPCR) and western blot, respectively. Flow cytometry was utilized to analyze cell apoptosis/cycle of HTR-8/SVneo cells. Additionally, the Transwell/wound healing assays were employed to assess invasion/migration of HTR-8/SVneo cells. Student’s t-test was employed to compare measurement data of normal distribution between two groups. Results: In placental tissues of women with LOPE, FOXA1 exhibited downregulation when compared to the normal controls. No significant differences were observed in pregnancy duration, maternal age, delivery times, or 1- and 5-minute Apgar scores between the two groups. However, the LOPE group had a significantly shorter gestational week at delivery, higher systolic and diastolic blood pressure, the presence of 24-hour proteinuria, lower neonatal birth weight, and lower placental weight. FOXA1 overexpression altered the cell cycle of trophoblasts, increasing the population in the S phase and decreasing it in the G2/M phase, with no effect on the G0/G1 phase. It did not affect trophoblast apoptosis. Furthermore, FOXA1 overexpression enhanced trophoblast invasive ability and migration. However, FOXA1 overexpression did not affect the mRNA expression levels of N-cadherin, vimentin, and fibronectin in trophoblast cells. Conclusions: In summary, our findings indicate that FOXA1 was underexpressed in the placental tissues of women with LOPE. Furthermore, the overexpression of FOXA1 led to significant changes in the trophoblast cell cycle and substantially enhanced trophoblast invasion and migration capabilities.